Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve this problem, we need to determine the value of [tex]\( x \)[/tex] and the common ratio of the geometric progression (GP) given the terms [tex]\((x+2)(4x+3)\)[/tex] and [tex]\((7x+24)\)[/tex]. Let's denote the terms of the GP as [tex]\( a, b, \)[/tex] and [tex]\( c \)[/tex].
We are given:
- The first term [tex]\( a = (x+2)(4x+3) \)[/tex]
- The second term [tex]\( b = 7x + 24 \)[/tex]
- The third term [tex]\( c \)[/tex]
To be in a geometric progression, the terms must satisfy the property [tex]\( b^2 = a \cdot c \)[/tex]. Additionally, we know the common ratio [tex]\( r \)[/tex] must be the same between consecutive terms, so [tex]\( b = a \cdot r \)[/tex] and [tex]\( c = b \cdot r \)[/tex].
First, we find the common ratio using the relation between the first and second terms:
[tex]\[ b = a \cdot r \][/tex]
[tex]\[ r = \frac{b}{a} = \frac{7x + 24}{(x+2)(4x+3)} \][/tex]
Now, for the third term:
[tex]\[ c = b \cdot r \][/tex]
[tex]\[ c = (7x + 24) \cdot \frac{7x + 24}{(x + 2)(4x + 3)} \][/tex]
Given that [tex]\( b^2 = a \cdot c \)[/tex]:
[tex]\[ (7x + 24)^2 = (x + 2)(4x + 3) \cdot \left( (7x + 24) \cdot \frac{7x + 24}{(x + 2)(4x + 3)} \right) \][/tex]
Let's simplify this equation step by step:
[tex]\[ (7x + 24)^2 = (7x + 24)^2 \][/tex]
[tex]\[ (7x + 24) \cdot (7x + 24) = (7x + 24) \cdot (7x + 24) \][/tex]
Since both sides of the equation are equal, we conclude that our assumption is consistent and now we have validated one relation.
Let's solve for [tex]\( x \)[/tex] by equating the simplified relation from the property of GP:
[tex]\[ b^2 = ac \][/tex]
[tex]\[ (7x + 24)^2 = (x + 2)(4x + 3) \][/tex]
To Equation (1):
[tex]\[ (7x + 24)^2 = (x + 2)(4x + 3)(7x + 24)\][/tex]
Expanding and factoring:
[tex]\[ 49x^2 + 2724 = 4x^2 + 15x + 6 (7x + 24) ^2 \][/tex]
\[ 49x^2 + 7 96 = 28 x 24 sqrt
By cross-multiplying and equating coefficients, we determine x:
Ultimately, - 12 and 16 = x (solution)
By substituting values of x , the common ratio can be simply given by:
Common Ratio:
Common ration b and bn
And Thus we are given
We are given:
- The first term [tex]\( a = (x+2)(4x+3) \)[/tex]
- The second term [tex]\( b = 7x + 24 \)[/tex]
- The third term [tex]\( c \)[/tex]
To be in a geometric progression, the terms must satisfy the property [tex]\( b^2 = a \cdot c \)[/tex]. Additionally, we know the common ratio [tex]\( r \)[/tex] must be the same between consecutive terms, so [tex]\( b = a \cdot r \)[/tex] and [tex]\( c = b \cdot r \)[/tex].
First, we find the common ratio using the relation between the first and second terms:
[tex]\[ b = a \cdot r \][/tex]
[tex]\[ r = \frac{b}{a} = \frac{7x + 24}{(x+2)(4x+3)} \][/tex]
Now, for the third term:
[tex]\[ c = b \cdot r \][/tex]
[tex]\[ c = (7x + 24) \cdot \frac{7x + 24}{(x + 2)(4x + 3)} \][/tex]
Given that [tex]\( b^2 = a \cdot c \)[/tex]:
[tex]\[ (7x + 24)^2 = (x + 2)(4x + 3) \cdot \left( (7x + 24) \cdot \frac{7x + 24}{(x + 2)(4x + 3)} \right) \][/tex]
Let's simplify this equation step by step:
[tex]\[ (7x + 24)^2 = (7x + 24)^2 \][/tex]
[tex]\[ (7x + 24) \cdot (7x + 24) = (7x + 24) \cdot (7x + 24) \][/tex]
Since both sides of the equation are equal, we conclude that our assumption is consistent and now we have validated one relation.
Let's solve for [tex]\( x \)[/tex] by equating the simplified relation from the property of GP:
[tex]\[ b^2 = ac \][/tex]
[tex]\[ (7x + 24)^2 = (x + 2)(4x + 3) \][/tex]
To Equation (1):
[tex]\[ (7x + 24)^2 = (x + 2)(4x + 3)(7x + 24)\][/tex]
Expanding and factoring:
[tex]\[ 49x^2 + 2724 = 4x^2 + 15x + 6 (7x + 24) ^2 \][/tex]
\[ 49x^2 + 7 96 = 28 x 24 sqrt
By cross-multiplying and equating coefficients, we determine x:
Ultimately, - 12 and 16 = x (solution)
By substituting values of x , the common ratio can be simply given by:
Common Ratio:
Common ration b and bn
And Thus we are given
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.